EVALUATION OF THE PERFORMANCE OF SEMI-GOVERNMENTAL INSTITUTIONS USING FINANCIAL ANALYSIS TECHNIQUES / CASE STUDY OF CONSULTING OFFICES / UNIVERSITY OF THIQAR - Suhair Kadhim Abdulkareem (Scholar Express Journals, 2024)
The research aims to identify the nature of semi-governmental institutions, identify financial analysis techniques, and demonstrate the extent to which they can be used in evaluating the performance of these institutions through describing and analyzing the financial statements of semi-governmental institutions/consulting offices. In order to achieve the research objectives, the researcher studied and analyzed the actual reality of the financial statements of the engineering consulting office for the period (2019 - 2021) using a set of financial analysis techniques, the most important of which are (vertical analysis, horizontal analysis, financial ratios, and the Althman model). A set of conclusions were reached, the most important of which are: Financial analysis techniques are used to analyze the financial data, represented by the financial statements available to institutions, and to study the financial information generated from the analysis of that data using the selected techniques, represented by financial ratios, in order to identify the financial performance of the institution that is the research sample. Among the most important recommendations that were developed are: The engineering consulting office should follow financial analysis in order to evaluate its financial performance by using various financial analysis techniques. The engineering consulting office should establish an administrative unit managed by specialists in the field of financial analysis who apply financial analysis techniques in order to evaluate the current financial performance and evaluate it towards addressing Weaknesses, maintaining and developing strengths, as well as benefiting from future investment opportunities and facing the challenges of the external environment.
Keywords: Semi-Governmental Institutions; Financial Performance Evaluation; Financial Analysis Techniques